A comparative study on the corrosion behaviour of welded and un-welded API 5L X70 steel in simulated fuel grade ethanol. Issue 1 (1st January 2022) - Joseph, O. O.; Fayomi, O. S. I.; Joseph, Olakunle O.; Afolalu, S. A.; Mubaiyi, M. P.; Olotu, O. N.; Fashola, J. O.
Abstract: In a bid to mitigate global warming, fuel grade ethanol (FGE) is being increasingly used in the fuel industry. However, there are material compatibility issues. In this study, the effect of Simulated Fuel Grade Ethanol (SFGE) on welded and un-welded API 5 L X-70 pipeline was investigated via gravimetric technique. Mass loss tests showed that the lowest corrosion rate was recorded in E10, whereas the highest corrosion rate was recorded in E40 environment. Statistical analysis reveals that on the basis of two-factor analysis of variance (ANOVA) test results, exposure time, and ethanol concentration significantly affected the corrosion rates of welded and unwelded X70 steel. Morphological examination revealed increased corrosion with an increase in ethanol concentration for welded X70 steel, which compares well with the results from mass loss tests.